Ideology Contestation in Management of University Library Development - Laugu, Nurdin (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2019)
Library collection development is mostly studied as professionalism based on a positivistic paradigm neglecting constructivist based paradigm. This constructivist base is reflected in various factors, such as ideology and commodification, which influence collection development. This research aims to investigate ideological contestation and commodification of institutions and audiences related to the collection development of Muhammadiyah University library. The ideological contestation was examined using Giddens’ structuration and Bourdieu’s habitus. The research data was collected from interviews with five informants from librarians and library directors. The data were supported by observation and documentation. The data obtained were analyzed using the Miles and Huberman technique based on three stages: reduction, display, and conclusion/verification. The results of the research found three formations in contestation, i.e. internal institutions, external institutions, and professionalism of librarians. The internal institution represented by the UMY Library encountered with outside institutions, such as American Corner, Iranian Corner, and publishers. Meanwhile, librarians show their professionalism in facing the ideological domination of those institutions through various strategies regarding the development of library collection.